A Family of Optimal Cubic-Order Multiple-root Solvers and Their Dynamics (European Journal of Pure and Applied Mathematics, 2023)
The complex dynamical analysis of the cubic-order iterative family is proposed to draw the fractal images via Möbius conjugacy map applied to a quadratic polynomial $(z-A) (z-B)$. The resulting dynamics is clearly visualized through various stability surfaces and parameter spaces using Mathematica.
Keywords: multiple-root solver; cubic-order; conjugacy; parameter space